The management of the hepatic artery thrombosis after liver transplantation - V. L. Korobka; M. Yu. Kostrykin; O. V. Kotov; R. O. Dabliz; E. S. Pak (Трансплантология (Москва), 2020)
The clinical case of liver revascularization in a recipient using the technique of selective thrombolysis of the hepatic artery and its stenting at the arterial anastomosis site has been reported. The applied technique allowed a quick elimination of thrombosis and stenosis of the arterial anastomosis, providing a long-term effect, preventing more severe consequences for the recipient, and saving the liver graft. The presented case showed that the combined technique of endovascular intervention might be a good alternative to the reconstruction of arterial anastomosis by re-exploration and by liver retransplantation.